Pengaruh Pelatihan, Reward dan Self Efficacy terhadap Kemampuan Kerja Driver Taxi PT. XYZ - Diana Ulki Rahayu; Ika Suhartanti Darmo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Sophisticated technology is not in line with the capabilities of existing Human Resources. Human resources are needed to be able to manage management properly. Human Resource Management (HRM) refers to policies, as well as systems that influence the behavior, attitudes and performance of employees so that they can compete in the current era of globalization. Problems that exist in PT. XYZ in this study is that the rewards given by the company to employees are still unable to spur on improving the performance of each employee. In addition, employees have not been fully convinced of the capabilities within them to achieve the targets set. This study aims to see whether there is an influence between training, reward and self efficacy on employee work ability. Quantitative research method using a questionnaire involving 55 respondents in June 2018. The results of this study stated that training, reward and self efficacy had a positive and significant effect on work ability.